2021
DOI: 10.7759/cureus.17837
|View full text |Cite
|
Sign up to set email alerts
|

SARS-COV-2 Infection in Children and Red Blood Cell Distribution Width

Abstract: SARS-COV-2 infection due to Coronavirus is highly contagious and causes varying degrees of illness throughout the world. Recent literature has shown an association between red blood cell distribution width (RDW) and adverse outcomes among adult patients with COVID-19. Multiple hypotheses can explain the potential prognostic role of RDW in COVID-19 infection.The aim of this study is to describe RDW values in SARS-COV-2 infected children admitted to the Pediatric Emergency Department to shed light on the potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Numerous studies have shown that RDW is an independent prognostic factor for adults admitted to emergency departments 3,28,29 . Contrary to what was observed in adults, no significant relationship has been demonstrated between RDW and hospitalization for COVID‐19 or MIS‐C in the pediatric age group 30 . The hemopoietic system is affected by aging, especially in terms of bone marrow cellularity, but these effects become apparent after the age of 65 years.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Numerous studies have shown that RDW is an independent prognostic factor for adults admitted to emergency departments 3,28,29 . Contrary to what was observed in adults, no significant relationship has been demonstrated between RDW and hospitalization for COVID‐19 or MIS‐C in the pediatric age group 30 . The hemopoietic system is affected by aging, especially in terms of bone marrow cellularity, but these effects become apparent after the age of 65 years.…”
Section: Discussionmentioning
confidence: 96%
“… 3 , 28 , 29 Contrary to what was observed in adults, no significant relationship has been demonstrated between RDW and hospitalization for COVID‐19 or MIS‐C in the pediatric age group. 30 The hemopoietic system is affected by aging, especially in terms of bone marrow cellularity, but these effects become apparent after the age of 65 years. This suggests that RDW may be a stronger prognostic factor in COVID‐19‐infected adults than in infants, whose bone marrow can rapidly replace defective RBCs.…”
Section: Discussionmentioning
confidence: 99%
“…Being able to identify symptom clustering and how they are related to disease severity and outcome may help implement a clinical bedside approach which may prove to be more useful than a radiological one in predicting child management and allowing a better resource allocation. [17,23]…”
Section: Discussionmentioning
confidence: 99%
“…Being able to identify symptom clustering and how they are related to disease severity and outcome may help implement a clinical bedside approach which may prove to be more useful than a radiological one in predicting child management and allowing a better resource allocation. [17,23] Regarding VL values, the literature data show contrasting evidence on the VL association with disease severity [24][25][26][27] or age. [28][29][30] Studies in children are limited to a small population with conflicting results about the comparability of VL in children with COVID-19, despite well-defined cohorts of adult studies.…”
Section: Discussionmentioning
confidence: 99%